2006
DOI: 10.1002/hed.20385
|View full text |Cite
|
Sign up to set email alerts
|

Black thyroid resulting from short-term doxycycline use: Case report, review of the literature, and discussion of implications

Abstract: Black thyroid is rare and only previously associated with chronic minocycline ingestion. This report documents a black thyroid in a patient after short-term exposure to doxycycline. Pigment accumulation in normal tissue is thought to occur by inhibition of thyroid peroxidase. Minocycline is a competitive inhibitor of this enzyme in its native configuration. Thyroid carcinomas are known to have abnormal thyroid peroxidase, which could account for reports of hypopigmented tumors within grossly darkened thyroid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…All hospitalized subjects had antibiotic use within six months of serum sample collection, while 47.2% of ambulatory subjects had recent antibiotic use. None of the subjects who received antibiotics received doxycycline, a tetracycline antibiotic known to cause black deposition in the thyroid gland (13). Other demographic characteristics were similar between the two groups.…”
Section: Resultsmentioning
confidence: 97%
“…All hospitalized subjects had antibiotic use within six months of serum sample collection, while 47.2% of ambulatory subjects had recent antibiotic use. None of the subjects who received antibiotics received doxycycline, a tetracycline antibiotic known to cause black deposition in the thyroid gland (13). Other demographic characteristics were similar between the two groups.…”
Section: Resultsmentioning
confidence: 97%
“…A recent review by Oertel and colleagues has identified 61 cases that have been reported to date [1]. Since the first report of black thyroid in human tissue [2], the etiology has been associated with minocycline ingestion for year or more [2, 3]. Although minocycline has been suggested as the cause of the pigmentation in many cases [46], it has also been noted to occur subsequent to infection [7], perhaps due to treatment with other tetracycline derivatives [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to its effects on the thyroid, minocycline is known to cause blueblack pigmentation of the skin, teeth, nails, and bone, with cutaneous effects being the most commonly observed. 3 Classically, black thyroid has been associated with the administration of high doses of minocycline, with most patients using the drug for more than 1 year before being diagnosed as having black thyroid. 3 Classically, black thyroid has been associated with the administration of high doses of minocycline, with most patients using the drug for more than 1 year before being diagnosed as having black thyroid.…”
mentioning
confidence: 99%